Efficacy of Tenofovir in Adefovir-Experienced Patients Compared with Treatment-Naive Patients with Chronic Hepatitis B. Issue 6 (August 2014) - Keskin, Onur; Örmeci, Asli Ç; Baran, Bülent; Kabaçam, Gökhan; Tüzün, Ali; Karatayli, Ersin; Akyüz, Filiz; Karatayli, Senem; Bozdayi, A Mithat; Önel, Derya; Badur, Selim; Idilman, Ramazan; et al.
Background: Tenofovir (TDF) has similar antiviral efficacy in both treatment-naive and lamivudine-resistant chronic hepatitis B (CHB) patients. Data on TDF use in patients with adefovir (ADV) resistance is inconsistent. The aim of our study was to assess antiviral efficacy of TDF against nucleoside analogue-naive (NN) and ADV-resistant (ADV-R) CHB and suboptimal responders to ADV (ADV-S). Methods: A database of 135 CHB patients treated with TDF was analysed. A total of 37 patients with incomplete data were excluded and analysis was performed in 98 (44 NN, 30 ADV-R and 24 ADV-S). Patients with primary ADV-R mutations had either A181T/V or N236T mutations or both. HBV DNA was measured at 3-month intervals until month 24. Primary outcome measures were comparison of the decline of HBV DNA between the three treatment groups. Results: NN patients had higher baseline HBV DNA compared with ADV-R and ADV-S patients (6.08 log10 IU/ml versus 5.53 and 4.88, respectively; P =0.002). By exponential regression analysis, HBV DNA decline kinetics differed between the three groups. HBV DNA decline was faster in NN patients compared to ADV-R and ADV-S CHB patients ( P =0.002 and P =0.004, respectively). Undetectable HBV DNA was achieved in 77.2%, 60% and 75% of NN, ADV-R and ADV-S CHB patients, respectively, at month 12 ( P = not significant). Conclusions: HBV DNA decline is slower in ADV-experienced patients compared with treatment-naive patients. The clinical significance of this slow response may be important in patients with critical liver reserve and high viral load. Optimal combination treatment (TDF+ entecavir) could be considered in these patients.